Catalytic Effects in Lithium–Sulfur Batteries: Promoted Sulfur Transformation and Reduced Shuttle Effect. Issue 1 (5th September 2017) - Liu, Donghai; Zhang, Chen; Zhou, Guangmin; Lv, Wei; Ling, Guowei; Zhi, Linjie; Yang, Quan‐Hong
Abstract: Lithium–sulfur (Li–S) battery has emerged as one of the most promising next‐generation energy‐storage systems. However, the shuttle effect greatly reduces the battery cycle life and sulfur utilization, which is great deterrent to its practical use. This paper reviews the tremendous efforts that are made to find a remedy for this problem, mostly through physical or chemical confinement of the lithium polysulfides (LiPSs). Intrinsically, this "confinement" has a relatively limited effect on improving the battery performance because in most cases, the LiPSs are "passively" blocked and cannot be reused. Thus, this strategy becomes less effective with a high sulfur loading and ultralong cycling. A more "positive" method that not only traps but also increases the subsequent conversion of LiPSs back to lithium sulfides is urgently needed to fundamentally solve the shuttle effect. Here, recent advances on catalytic effects in increasing the rate of conversion of soluble long‐chain LiPSs to insoluble short‐chain Li2 S2 /Li2 S, and vice versa, are reviewed, and the roles of noble metals, metal oxides, metal sulfides, metal nitrides, and some metal‐free materials in this process are highlighted. Challenges and potential solutions for the design of catalytic cathodes and interlayers in Li–S battery are discussed in detail. Abstract : Lithium–sulfur (Li–S) battery has emerged as one of the most promising next‐generation energy‐storage systems. The catalytic effect on propelling the conversion of soluble long‐chain lithium polysulfides and insoluble low‐chain Li2 S2 /Li2 S is an important procedure for developing practically useable Li–S battery.